Structural Characterization of Membrane-Electrode-Assemblies in High Temperature Polymer Electrolyte Membrane Fuel Cells. Issue 14 (7th October 2019) - Bodner, Merit; Bentzen, Janet Jonna; Dahl, Vedrana Andersen; Alfaro, Silvia M.; Steenberg, Thomas; Hjuler, Hans Aage; Simonsen, Søren Bredmose
Abstract : In high temperature polymer electrolyte fuel cells, polybenzimidazole membranes doped in phosphoric acid are used as electrolyte material. The membrane thickness directly relate to the amount of absorbed acid which relate to performance. In this study, we compare scanning electron microscopy and X-ray micro-computed tomography (CT) regarding suitability for determining the structure of electrolyte membranes. Semi-automated layer identification and thickness estimation was used to reduce human errors and data processing time. Scanning electron microscopy was found reliable for membrane thickness characterization despite necessary destructive sample preparation. With X-ray CT it was possible to study the cells non-destructively before and after cell test. This made it possible to identify, so-called hot pressing, as the step in which the membrane lost most of its thickness. After cell operation, the use of X-ray CT at large field of view and a recently developed layer detection algorithm made it possible to visualize compression of the membrane in a pattern identical to that of the flow plate channels. This compression pattern would have been difficult to determine with conventional electron microscopy or X-ray CT without semi-automated layer detection.